2007
DOI: 10.1111/j.1551-2916.2007.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Release From Tungstate and Titanate Waste Form Materials in Simulated Canister Corrosion Product‐Containing Solutions

Abstract: The leaching of two potential 137Cs waste form ceramics (Cs‐containing hexagonal tungsten bronze (HTB) and hollandite) has been investigated in Fe(NO3)3 solutions of increasing concentration at 150°C over a period of 4 days. These ceramics contain within their structures reduced Mo5+/W5+ and Ti3+ species for the HTB and hollandite, respectively, which therefore might render them susceptible to oxidation‐induced leaching. Elucidation of the extent and the mechanism of leaching of the Cs from these ceramics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…315 The oxidation-induced leaching of Cs from Cs-hollandite (upon Ti 3+ oxidation for charge balance) was also reported with the presence of redox-active iron species from canister corrosion, e.g., Fe 3+ , NO 3− , or by radiation hydrolysis, implying a potential degradation mechanism and accelerated corrosion when interacting with a corroding canister. 316 3.5.3. Degradation of Pyrochlore Waste Forms and Impact of Material Parameters and Structure.…”
Section: Modeling Of Chemical Durability and Dissolution Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…315 The oxidation-induced leaching of Cs from Cs-hollandite (upon Ti 3+ oxidation for charge balance) was also reported with the presence of redox-active iron species from canister corrosion, e.g., Fe 3+ , NO 3− , or by radiation hydrolysis, implying a potential degradation mechanism and accelerated corrosion when interacting with a corroding canister. 316 3.5.3. Degradation of Pyrochlore Waste Forms and Impact of Material Parameters and Structure.…”
Section: Modeling Of Chemical Durability and Dissolution Kineticsmentioning
confidence: 99%
“…In addition to the ion-exchange mechanism, a redox reaction could also occur upon the oxidation of Ti 3+ to Ti 4+ by the oxidizing acid (e.g., Cs 0.8 Ba 0.4 Ti 8 O 16 in dilute nitric acid, 200 °C, 4 days), and the complete extraction of Cs + out of the open channels destabilized the hollandite open-frame structure, resulting in the surface alteration products of rutile and brookite . The oxidation-induced leaching of Cs from Cs-hollandite (upon Ti 3+ oxidation for charge balance) was also reported with the presence of redox-active iron species from canister corrosion, e.g., Fe 3+ , NO 3– , or by radiation hydrolysis, implying a potential degradation mechanism and accelerated corrosion when interacting with a corroding canister …”
Section: Corrosion Of Crystalline Ceramics In Aqueous Environmentsmentioning
confidence: 99%
“…This is a mechanism similar to what was hypothesized by Lutze and Grambow 80 and has been briefly reviewed in Section "Glass and aqueous Fe 2+ /Fe 3+ cations". For instance, Luca et al demonstrated that the presence of aqueous Fe 3+ enhanced the dissolution of two redox active and semiconducting ceramic waste forms (in an oxic condition), including Cs-containing hexagonal tungsten bronze and hollandite 84 . The authors suggested that the Ti 3+ and Mo 5+ /W 5+ species present in the ceramics can be oxidized by aqueous Fe 3+ , thus facilitating the structure collapse and/or ion-exchange that eventually leads to the enhanced corrosion of the ceramics.…”
Section: Glass and Steel Corrosion Productsmentioning
confidence: 99%
“…For example, in perovskites [61,62], the alkaline cations (Ca 2+ /Sr 2+ ) are initially discharged out in larger amounts upon aqueous attack, followed by drop in the release rates due to the formation of a Ti–O passive layer. On the other hand, hollandite structure's durability, with mixed octahedral cations, is highly sensitive to the stoichiometry [6367]. (Ba,Al)-hollandite, when exposed to aqueous solution, forms a Al(Ti)-rich surface layer, either amorphous or crystalline Al(OH) n (3− n )+ , which is more stable and protective than the Ti–O layer even in the most severe hydrothermal conditions rendering higher durability compared to perovskites [63,64,68].…”
Section: Hollandites As Nuclear Waste Formsmentioning
confidence: 99%